Pharmacoepidemiology: A time for a new multidisciplinary approach to precision medicine. Issue 8 (7th April 2021) - Issa, Amalia M.; Carleton, Bruce; Gerhard, Tobias; Filipski, Kelly K.; Freedman, Andrew N.; Kimmel, Stephen; Liu, Geoffrey; Longo, Cristina; Maitland‐van der Zee, Anke H.; Sansbury, Leah; Zhou, Wei; Bartlett, Gillian
Abstract: The advent of the genomic age has created a rapid increase in complexity for the development and selection of drug treatments. A key component of precision medicine is the use of genetic information to improve therapeutic effectiveness of drugs and prevent potential adverse drug reactions. Pharmacoepidemiology, as a field, uses observational methods to evaluate the safety and effectiveness of drug treatments in populations. Pharmacoepidemiology by virtue of its focus, tradition, and research orientation can provide appropriate study designs and analysis methods for precision medicine. The objective of this manuscript is to demonstrate how pharmacoepidemiology can impact and shape precision medicine and serve as a reference for pharmacoepidemiologists interested in contributing to the science of precision medicine. This paper depicts the state of the science with respect to the need for pharmacoepidemiology and pharmacoepidemiological methods, tools and approaches for precision medicine; the need for and how pharmacoepidemiologists use their skills to engage with the precision medicine community; and recommendations for moving the science of precision medicine pharmacoepidemiology forward. We propose a new integrated multidisciplinary approach dedicated to the emerging science of precision medicine pharmacoepidemiology.